Human newborns form musical predictions based on rhythmic but not melodic structure - Bianco, Roberta; Tóth, Brigitta; Bigand, Felix; Nguyen, Trinh; Sziller, István; Háden, Gábor P.; Winkler, István; Novembre, Giacomo (PLOS Biology, 2026)
The ability to anticipate musical structure is a fundamental human trait, but whether it exists at birth is unclear. This study shows that newborns encode rhythmic expectations based on statistical regularities in real music, while melodic tracking is absent, suggesting rhythm-driven predictive processing from birth.